Impact of soybean-associated plant growth-promoting bacteria on plant growth modulation under alkaline soil conditions - Mariana Roriz; Sofia I.A. Pereira; Paula M.L. Castro; Susana M.P. Carvalho; Marta W. Vasconcelos (Heliyon, 2023)
Conventional strategies to manage iron (Fe) deficiency still present drawbacks, and more eco-sustainable solutions are needed. Knowledge on soybean-specific diversity and functional traits of their plant growth-promoting bacteria (PGPB) potentiates their applicability as bioinoculants to foster soybean performance under calcareous soil conditions. This work aimed to assess the efficacy of PGPB, retrieved from soybean tissues/rhizosphere, in enhancing plant growth and development as well as crop yield under alkaline soil conditions.Seventy-six bacterial strains were isolated from shoots (18%), roots (53%), and rhizosphere (29%) of soybean. Twenty-nine genera were identified, with Bacillus and Microbacterium being the most predominant. Based on distinct plant growth-promoting traits, the endophyte Bacillus licheniformis P2.3 and the rhizobacteria Bacillus aerius S2.14 were selected as bioinoculants.In vivo tests showed that soybean photosynthetic parameters, chlorophyll content, total fresh weight, and Fe concentrations were not significantly affected by bioinoculation. However, inoculation with B. licheniformis P2.3 increased pod number (33%) and the expression of Fe-related genes (FRO2, IRT1, F6′H1, bHLH38, and FER4), and decreased FC-R activity (45%). Moreover, bioinoculation significantly affected Mn, Zn, and Ca accumulation in plant tissues.Soybean harbors several bacterial strains in their tissues and in the rhizosphere with capacities related to Fe nutrition and plant growth promotion. The strain B. licheniformis P2.3 showed the best potential to be incorporated in bioinoculant formulations for enhancing soybean performance under alkaline soil conditions.